Comparison of general anesthesia versus no anesthesia in elective transjugular intrahepatic portosystemic shunt (TIPS): Procedural and hemodynamic parameters - Ziad Maksoud; Michael Köhler; Gala Nacul Mora; Florian Möllmann; Max Masthoff; Rainer Eßeling; Patrick Strauß; Arne Meier; Markus Kimmann; Jonel Trebicka; Michael Praktiknjo; Gesa Helen Pöhler (PLoS ONE, 2026)
Transjugular intrahepatic portosystemic shunt (TIPS) is an established treatment for complications of portal hypertension; yet the influence of anesthesia modality on procedural performance and hemodynamics remains insufficiently characterized. This retrospective single-center study compared radiation exposure, procedural parameters, and portal hemodynamics between procedures performed with and without general anesthesia (GA). A total of 84 patients were identified, of whom 62 were age- and sex-matched into two equal groups: group 1 (GA, n = 31) and group 2 (no GA, n = 31). Evaluated parameters included length of hospital stay, dose area product (DAP), fluoroscopy time (FT), contrast volume, number of digital subtraction angiography series, procedure duration, and pre- and post-TIPS measurements of portal venous pressure, central venous pressure (CVP), and portosystemic pressure gradient (PPG). Non-parametric statistical tests were applied. Patients in group 1 had significantly shorter postoperative hospital stay (median 6 days; interquartile range (IQR): 4–7) than those in group 2 (8 days; IQR 6–8; p = 0.006). Radiation dose was significantly lower in group 1, with a median DAP of 127.1 Gy*cm 2 (IQR 64.6–201.8) compared to 325 Gy*cm 2 (IQR 162.3–393.7; p = 0.02) in group 2. FT was also reduced under GA (12.2 minutes; IQR 9.6–15.9 vs. 16.0 minutes; IQR 11.5–25.9; p = 0.01), as was contrast volume (75 ml; IQR 60–100 vs. 90 mL; IQR 60–110; p = 0.01). PPG reduction was achieved in both groups, despite higher CVP under GA. These findings suggest that GA may facilitate more stable procedural conditions during TIPS, reducing radiation dose and contrast use without compromising hemodynamic effectiveness.